Integrating Organizational Culture Management into School Governance: Evidence from Character Education Practices - Marsa Bila Mutsaqofah; Yohamintin (Universitas Nurul Jadid, 2025)
This study examines how integrating organizational culture management into school governance drives character education practices in elementary schools. Using a qualitative case study, we explore how governance routines and policies translate cultural values ​​into daily practices. We collected data through observations, in-depth interviews, and documentation, then analyzed the data using the Miles and Huberman model. The findings show that governance mechanisms such as morning gate routines, punctuality norms, collaborative planning, and parent–school communication institutionalize teacher role modeling and make it consistent across classrooms. These mechanisms shape students' politeness, discipline, responsibility, and cooperation. Teachers act as visible carriers of culture, and students at the elementary level imitate these concrete behaviors. Collaboration among teachers, students, and parents sustains the process beyond the classroom and reduces value gaps between school and home. The study concludes that managing organizational culture as part of school governance is more effective than purely normative instruction for strengthening character education. Practical implications include embedding clear routines, consequence systems, and joint evaluations into school policies to ensure continuity and scalability. This approach offers a contextual and sustainable pathway for character formation in the digital era.